Balance sheet effects of a currency devaluation: A stock-flow consistent framework for Mexico - Lorenzo Nalin; Giuliano Toshiro Yajima (Levy Economics Institute of Bard College, 2020)
This working paper empirically and theoretically analyzes the exchange rate's role in Mexico's development for the period 2004-19. We test the hypothesis of the re(emergence) of the balance sheet effect due to an increase in external debt in the nonfinancial corporate sector; higher foreign debt would affect private investment after episodes of real currency depreciation, in the spirit of the literature put forward by Gertler, Gilchrist, and Natalucci (2007) and Céspedes, Chang, and Velasco (2004). We build a stock-flow consistent (SFC) model, following the OPENFLEX model proposed in Godley and Lavoie (2006), to explore the balance sheet implications from a theoretical perspective. We simulate the 2014 fall in the Mexican peso generated by the drop in oil prices to replicate stylized facts for Mexico for the period under investigation. The scenario analysis points to a hysteresis effect of the real exchange rate (RER) depreciation on investment flows. That is, firms' investment ratio does not completely recover from negative shocks in the currency.
Keywords: F37; F31; E7; 330; International Finance Forecasting and Simulation; Models; Applications; Foreign Exchange; Macro-Based Behavioral Economics